2011
DOI: 10.1246/bcsj.20110012
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions in Soft Matter Induced by Selective Solvation

Abstract: We review our recent studies on selective solvation effects in phase separation in polar binary mixtures with a small amount of solutes. Such hydrophilic or hydrophobic particles are preferentially attracted to one of the solvent components. We discuss the role of antagonistic salt composed of hydrophilic and hydrophobic ions, which undergo microphase separation at wateroil interfaces leading to mesophases. We then discuss phase separation induced by a strong selective solvent above a critical solute density n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(78 citation statements)
references
References 108 publications
(212 reference statements)
0
78
0
Order By: Relevance
“…In liquid water in contact with a hydrophobic surface, water molecules tend to be separated from the surface due to the hydrogen bonding among the water molecules, resulting in the formation of a gaseous layer on the surface 5 . In aqueous mixtures with salt, prewetting behavior is much intensified by the composition-dependent surface ionization and the preferential solvation of ions [6][7][8] . In these examples, heterogeneities in the density or the composition are induced near the wall, often resulting in wetting or drying transition on the wall.…”
Section: Introductionmentioning
confidence: 99%
“…In liquid water in contact with a hydrophobic surface, water molecules tend to be separated from the surface due to the hydrogen bonding among the water molecules, resulting in the formation of a gaseous layer on the surface 5 . In aqueous mixtures with salt, prewetting behavior is much intensified by the composition-dependent surface ionization and the preferential solvation of ions [6][7][8] . In these examples, heterogeneities in the density or the composition are induced near the wall, often resulting in wetting or drying transition on the wall.…”
Section: Introductionmentioning
confidence: 99%
“…(i) Near the critical point, a mixture solvent is very sensitive to selective impurities such as ions which interact with each solvent species asymmetrically. [30][31][32] Theoretical works have shown that even a small amount of salt can play a significant role in the static behavior of the adsorption layer. [33][34][35] The ion effect on the drag coefficient would be significant in experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Then g i > 0 for hydrophilic ions and g i < 0 for hydrophobic ions. For strongly hydrophilic ions, μ i sol (φ) should decrease very steeply in a concentration range 0 < φ < φ i sol , where hydration shells are formed [4]. Here φ i sol ∼ 0.002 for Br − in water-nitrobenzene.…”
Section: Introductionmentioning
confidence: 99%
“…Jpn. 81 (2012) SA004 SA004-2 coexistence curve [11,12], and (iii) mesophase formation in aqueous mixtures for an antagonistic salt [2][3][4][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation